The Utilization of Hand Soap for Hand Washing and Family Latrine Ownership as Preventive Measures Against Stunting in Infants and Toddlers in the Parigi Moutong District of Central Sulawesi Province - Bungawati, Bungawati; Hasanudin; Maryam; Amsal; Saharudin; Ratman (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
Stunting is a malnutrition condition in children under five, characterized by delayed growth and inappropriate height. Environmental factors, such as nutrition, digestive infections, low birth weight, and poor environmental sanitation, indirectly impact the health of children under five, affecting their nutritional status. This research aims to determine the level of knowledge, ownership of toilets, and hand washing habits as factors for preventing stunting in the working area of the Ampibabo Community Health Center. The study used an analytical observational research with a case-control design, with 70 respondents consisting of mothers of babies and toddlers. The results showed a relationship between knowledge, latrine ownership, and hand washing habits and stunting incidence in babies and toddlers. This suggests that community health centers should provide regular and continuous assistance to cadres in providing education about stunting prevention at all levels of society, especially those without family toilets and without soap-washing habits.